KONSTRUKSI SOSIAL PEREMPUAN DALAM KEKERASAN RUMAH TANGGA DI BANJARNEGARA, JAWA TENGAH - Mutoharoh, Mutoharoh (Jurnal Sosiologi Agama, 2017)
Marriage is something wishful many people to be found happiness inside, life together with loveliness and make a contract. Unfortunately, not forever a domestic trip to be present in space happiness. Fact in societal, occurred a domestic violence. Domestic violence occurred by husband to wife. The subject or doer of violence is not people without religion or not understand with the doctrine in religion. Unfortunately, although in religion measure domestic violence is not legal but it’s always present. Sokanandi RT 05 RW III Banjarnegara it’s one of territory with quantity domestic violence exactly tall, however attention at this case rarely finished. Consequently, this research purpose to understand how about social construction wife in family, cause occur domestic violence, and shape domestic violence happened. This research is qualitative research with analytic-descriptive approach. Accumulation data used observation method, interview, and documentation. The primary source from result observation and result interview it’s from official Religious Courts of Banjarnegara, village head’s office of Sokanandi, RT, ustadz, and respondent domestic violence. The secondary source included from document, website, and competent books. The analysis data use three phases, which is reductions data, display data, and verification data. Researcher use gender theory and feminism as instrument to analyze. Keywords: Social Construction, Domestic Violence, Female